SISTEM INFORMASI BARANG KADALUARSA DENGAN METODE EXTREAM PROGRAMING STUDI KASUS CABANG ALFAMART FATMAWATI - Gusti Kanuraga (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The development of technology is currently growing rapidly in the field of information technology and the Internet, especially web-based information systems. Advances in information technology today have many benefits. Utilization of information technology can help all types of businesses improve the efficiency and effectiveness of business processes, managerial decision making and teamwork. Improvements are really felt to occur in the development of information technology, for example, from information gathering, information processing, to information distribution. This occurs due to the desire to obtain fast and accurate information. The research method used is experimental, meaning that the research is conducted to conduct trials on certain problems with the use of certain theories so that the correct test results are obtained between the problems taken and the theory used. The development model used in this research is extreme programming. The purpose and objective of this research is to change the method of checking expired goods which were previously still manually and transferred using a web-based system. Based on the results and discussion in this study, it can be concluded that the application of the extreme progriming method in building an information system on expired goods at the Alfamart Fatmawati branch can assist in handling expired goods more effectively and accurately.